Child Maltreatment in Western China: Demographic Differences and Associations with Mental Health - Zhou, Yueyue (Int J Environ Res Public Health, 2019)
Background: Child maltreatment has become a serious public health and social problem worldwide. However, knowledge regarding the status of child maltreatment in western China is limited. Objective: The objective of this study was to investigate the status of child maltreatment in western China and its relationship with mental health. Participants and setting: The present study evaluated child maltreatment in a sample of 1511 children (M(age) = 11.48 years) from western China. Methods: The participants completed questionnaires designed to collect demographic information and assess their experiences with maltreatment and symptoms of depression and anxiety. Results: In total, 12.3%, 14.0%, 1.3% and 28.1% of the children experienced physical abuse, emotional abuse, sexual abuse and neglect, respectively, while 186 children (12.3%) experienced multiple types of maltreatment. Boys were more likely to experience maltreatment than girls in most cases. Physical abuse, emotional abuse, sexual abuse and neglect had unique effects on depression symptoms. Physical abuse, emotional abuse and neglect, but not sexual abuse, had unique effects on anxiety symptoms. Conclusions: The children who experienced maltreatment had higher levels of depressive and anxiety symptoms. Population-based prevention and educational programs should highlight the serious negative effects of maltreatment, especially emotional abuse and neglect, which have long been ignored in China.